Production of biochar from tropical fruit tree residues and ecofriendly applications – A review. (May 2023) - Ding, Zheli; Ge, Yu; Gowd, Sarath C.; Singh, Ekta; Kumar, Vinay; Chaurasia, Deepshi; Kumar, Vikas; Rajendran, Karthik; Bhargava, Preeti Chaturvedi; Wu, Peicong; Lin, Fei; Harirchi, Sharareh; et al.
Graphical abstract: Highlights: Major promising tropical fruit tree residues for biochar production has been analyzed. Recent techniques for tropical fruit tree residues conversion have been discussed. Unique characteristics related to tropical fruits biochar production has been explored. Ecofriendly applications of biochar have been discussed. Major bottleneck and research gap has been presented. Abstract: Environmental contamination is considered a major issue with the growing urbanization and industrialization. In this context, the scientific society is engaged in searching for a sustainable, safe, and eco-friendly solution. Sustainable materials such as biochar play an important role in environmental contamination. It has some specific properties such as micropores which increase the surface area to bind the pollutants. This review endeavors to analyze the potential of fruit wastes especially tropical fruit tree residues as potential candidates for producing highly efficient biochar materials. The review discusses various aspects of biochar production viz. pyrolysis, torrefaction, hydrothermal carbonization, and gasification. In addition, it discusses biochar use as an adsorbent, wastewater treatment, catalyst, energy storage, carbon sequestration and animal feed. The review put forward a critical discussion about key aspects of applying biochar to the environment.